Neutrality of the State Civil Apparatus during the 2019 General Election in Majene City - Asriani (Kirana Publisher (KNPub), 2022)
This research was conducted in Majene Regency with the title Neutrality of the State Civil Apparatus during the 2019 General Elections in Majene City. The research approach used was descriptive qualitative research. Descriptive research aims to provide data as accurately as possible about a person, condition or other symptom. Descriptive research is research that aims to investigate situations, conditions, circumstances, events, activities, and others. The research results are presented in the form of a research report. Data collection techniques were carried out in three ways, namely library research, observation, and interviews. based on the results of the study showing the Neutrality of the State Civil Apparatus during the general election in Majene City in 2019, that in the 2019 Majene City Legislative Election, the ASN Secretariat of the Majene City DPRD office had not placed itself in a neutral position. This is because there are still ASNs who are indirectly involved in several political activities in the 2019 Majene City Legislative Election. The involvement of the ASN Secretariat of the Majene City DPRD office in the 2019 legislative elections is proof that the bureaucracy in Indonesia still cannot be categorized as an ideal bureaucracy. Because in reality the ASN Secretariat of the Majene City DPRD office has not been able to limit political interests with the duties that should be carried out as a servant of the state.